Genome-wide association studies of photosynthetic and agronomic traits in cowpea collection - Sansa, O.; Abberton, M.T.; Ariyo, J.; Paliwal, R.; Ige, A.; Dieng, I.; Ayo-Vaughan, M.; Olowe, V.I.; Oyatomi, O. (Oxford University Press, 2024)
Exploring genomic regions linked with drought tolerance and photosynthesis in cowpea could accelerate breeding of climate-resilient cowpea varieties. A genome-wide association study (GWAS) was conducted to identify marker–trait associations for agronomic and photosynthetic traits measured under well-watered and water-stressed conditions. One hundred and twelve cowpea accessions from IITA were phenotyped for agronomic and photosynthetic traits across 3 locations in 2 years: Ibadan, Ikenne (2020 and 2021), and Kano (2021 and 2022). The accessions were genotyped using 19,000 Diversity Arrays Technology sequencing single-nucleotide polymorphism (SNP) markers from which 9,210 markers were utilized for GWAS analysis using BLINK and linear mixed model (LMM) in GAPIT. Results revealed significant accession × environment interactions for measured traits, while ΦPSII, ΦNO, and ΦNPQ had significant and consistent correlations with grain yield across conditions. GWAS identified 5 SNP markers having consistent associations with grain yield under well-watered and water-stressed conditions and 3 markers associated with ΦNPQ and ΦNO. Gene annotations revealed Vigun04g169000 and Vigun08g168900 genes linked with grain yield and highly expressed under water-stressed conditions have functional roles in regulating plant development and adaptive response to environmental stress. Vigun07g133400, Vigun07g132700, and Vigun07g258000 genes linked with ΦNPQ and ΦNO are involved in activities controlling photoprotection and stress-induced damage in plants. This study identified natural genetic variation in cowpea and correlations between photosynthetic traits and grain yield under real-field drought conditions. The identified SNP markers upon validation would be valuable in marker-assisted selection and useful for cowpea breeders to harness the role of photosynthesis in genetic enhancement of cowpea’s tolerance to drought.